Hormone therapy improves conservation breeding outcomes in the critically endangered Baw Baw frog, Philoria frosti - Gilbert, Deon J.; Goodall, Damian; Byrne, Phillip G.; Silla, Aimee J. (Frontiers in Conservation Science, 2024)
Conservation breeding programs (CBPs) are often the lifeline between extinction and survival for many imperilled amphibian species. With the goal of recovering wild populations, CBP success is reliant on their ability to successfully manage ex-situ populations over time, breed viable offspring, and maintain genetic diversity. Reproductive technologies have emerged as important tools in the conservation toolkit to allow managers to improve reproductive output and genetic management, and their use in amphibian conservation is expanding. To date, studies investigating the efficacy of hormone therapies in amphibians typically only report spawning and fertility rates and do not monitor offspring to later stages of development. For the first time, we assess the effect of hormone therapies on breeding outcomes beyond oviposition, to metamorphosis, in the critically endangered Baw Baw frog, Philoria frosti. To determine the effect of hormone therapy on spawning success and offspring viability, male-female pairs were administered 0 µg/g gonadotropin-releasing hormone agonist (GnRHa), 0.5 µg/g GnRHa, or 0.5 µg/g GnRHa+10 µg/g metoclopramide (MET)(n=12 pairs/treatment), and the number of pairs ovipositing, time to oviposition, clutch size, metamorph mass, and the proportion and number (mean and total) of offspring to metamorphosis were quantified. Overall, the percentage of pairs that oviposited was high across all treatment groups (92-100%). The percentage of fertile clutches was highest in the GnRHa group (92%) and lowest in the GnRHa+MET group (82%), though differences were not statistically significant. Both hormone treatment groups took significantly less time to oviposit than the control pairs. Notably, the proportion of eggs developing to metamorphosis was significantly higher in the GnRHa group, resulting in 74% (total eggs=539) metamorphosing compared to approximately 50% in the control and GnRHa+MET treatments (total eggs=273 and 264, respectively). Interestingly, weight at metamorphosis was statistically similar across treatments, and results are consistent with previous studies in this species that show a narrow range in size at metamorphosis. The continued application of GnRHa is recommended to improve conservation outcomes for the critically endangered Baw Baw frog. The outcomes of this research advance our understanding of the impact of hormone therapies on reproductive outcomes and will inform amphibian conservation breeding programs globally.